Solutions to sustainability in construction : some examples - Chu, Jian (2018)
Many innovative solutions to sustainability have been developed or adopted in the past in various sectors of construction. Some of those related to geotechnical engineering are presented in this paper. These include the use of biocement as an alternative to Portland cement for soil improvement, the use of bio-desaturation as a method for mitigation of liquefaction hazard, the use of plastic waste to make construction products, and the use of the NEUSpace method for land reclamation in deep water to reduce the usage of fill materials.